Perforin-Like Proteins of Apicomplexan Parasites - Sassmannshausen, Juliane; Pradel, Gabriele; Bennink, Sandra (Frontiers in Cellular and Infection Microbiology, 2020)
Perforins are secreted proteins of eukaryotes, which possess a membrane attack complex/perforin (MACPF) domain enabling them to form pores in the membranes of target cells. In higher eukaryotes, they are assigned to immune defense mechanisms required to kill invading microbes or infected cells. Perforin-like proteins (PLPs) are also found in apicomplexan parasites. Here they play diverse roles during lifecycle progression of the intracellularly replicating protozoans. The apicomplexan PLPs are best studied in Plasmodium and Toxoplasma, the causative agents of malaria and toxoplasmosis, respectively. The PLPs are expressed in the different lifecycle stages of the pathogens and can target and lyse a variety of cell membranes of the invertebrate and mammalian hosts. The PLPs thereby either function in host cell destruction during exit or in overcoming epithelial barriers during tissue passage. In this review, we summarize the various PLPs known for apicomplexan parasites and highlight their roles in Plasmodium and Toxoplasma lifecycle progression.